1994
DOI: 10.1073/pnas.91.23.10957
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of the adenine-specific DNA methyltransferase M.Taq I in complex with the cofactor S-adenosylmethionine.

Abstract: The Thermus aualcus DNA methyltransferase M'Taq I (EC 2.1.1.72) methylates N6 of adenine in the specific double-helical DNA sequence TCGA by transfer of -CH3 from the cofactor S-adenosyl-L-methionine. The x-ray crystal structure at 2.4-A resolution of this enzyme in complex with S-adenosylmethlonlne shows a/P folding of the polypeptide into two domains of about equal size. They are arranged in the form of a C with a wide deft suitable to accommodate the DNA substrate. The N-terminal domain Is dominated by a ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
145
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(153 citation statements)
references
References 21 publications
6
145
0
Order By: Relevance
“…Such preferential interaction with AdoMet is in agreement with the preferred binding of AdoMet as compared with AdoHcy shown here. In agreement with these considerations, in all DNA MTases AdoMet adopts the extended conformation, and in the only examples where AdoMet and AdoHcy binding can be directly compared (M.TaqI and M.RsrI) AdoMet is extended whereas AdoHcy is folded (14,33). Therefore, the extended conformation most likely is the preferred conformation for AdoMet, whereas AdoHcy can adopt both the extended and the folded conformations in the binary complex.…”
Section: Discussionmentioning
confidence: 49%
“…Such preferential interaction with AdoMet is in agreement with the preferred binding of AdoMet as compared with AdoHcy shown here. In agreement with these considerations, in all DNA MTases AdoMet adopts the extended conformation, and in the only examples where AdoMet and AdoHcy binding can be directly compared (M.TaqI and M.RsrI) AdoMet is extended whereas AdoHcy is folded (14,33). Therefore, the extended conformation most likely is the preferred conformation for AdoMet, whereas AdoHcy can adopt both the extended and the folded conformations in the binary complex.…”
Section: Discussionmentioning
confidence: 49%
“…The highly conserved Asn in motif IV (Fig. 1) of the N-methyltransferase domains of peptide synthetases is also found in methyltransferases such as TaqI and glycine N-methyltransferase from rat (35,36,42). Cheng et al (13) have suggested that the side chain of Asn acts as a donor in a hydrogen bond to the target adenine and therefore allows direct transfer of the activated methyl group of AdoMet.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray structure determination of different methyltransferases revealed a considerable flexibility concerning the location of motif I in the polypeptide chains. In the case of the TaqI and HhaI DNA methyltransferases, motif I is located near the N terminus, forming the AdoMet-binding site, whereas the DNAbinding site is C-terminal (13,(35)(36)(37). In contrast, in the case of the PvuII DNA methyltransferase, motif I is located closer to the C terminus (38).…”
Section: Discussionmentioning
confidence: 99%
“…The product of ORF4 (named papM ) weakly resembled the TaqI methyltransferase from Thermophilus aquaticus (Barany et al, 1992) involved in the N-methylation of the adenine of the DNA recognition sequence. Careful sequence comparison with other S-adenosyl-L-methionine (SAM)-dependent methyltransferases revealed in PapM (amino acids 124 to 135) the conserved sequence rich in glycine residues (VLE/DXGXGXG) (Ingrosso et al, 1989) which forms part of the SAM-binding site in M-TaqI-AdoMet and M-HhaI-AdoMet crystalized complexes (Labahn et al, 1994;Cheng et al, 1993).…”
Section: Sequence Homology Studiesmentioning
confidence: 99%